The health promoting status of Saint Louis University, Baguio City - Bautista, Elizabeth H.
Rapid demographic changes have caused a shift in the disease patterns worldwide. These changes necessitated a transition in health care management from the traditional treatment, care and rehabilitation to prevention, control as well as re-orientation of health services. Thus the birth of the health promotion framework which include the concept of health promoting schools. This study focused on the description of the health promoting status of Saint Louis University (SLU) adopting relevant components of the WHO framework and other indicators of a health promoting school specific to the situation of the university. The study was conducted at SLU, Baguio City. The respondents were 356 students, 163 teachers and 81 administrative staff. Students considered in the study were those enrolled in any subject in any course at the time of data collection and belonging to the graduating class while for teachers and administrative staff, they should have provided services to SLU for at least five years. The descriptive comparative design, specifically the comparison of three groups was utilized. The instruments used to gather data were the questionnaire, the observation checklist and the structured interview guide. Data gathering was conducted from October 2002 to February 2003. The collected data were treated using ANOVA. The Scheffe's test was used to identify the groups where significant differences lie. Significant findings showed that students, teachers and administrative staff perceive SLU as moderately health promoting in terms of healthy school policy, social environment, community relations, personal health skills and health services. Students and teachers perceive SLU as moderate health promoting whereas the administrative staffs perceive SLU as highly health promoting in terms of indicator physical environment of the school. The findings also showed that students and administrative staffs use the mediating strategy "discussion of suggestions during meetings". In addition to this, the administrative staff also utilizes "voicing out of suggestions during meetings". As to the advocacy strategy, the findings also showed that students, teachers and administrative staff use "listening to the problems of colleagues and channeling it to the proper authorities". Aside from this, teachers and administrative staffs also use the strategy "getting the suggestions of colleagues and verbalizing it in the forum". As to enabling strategies, the findings also showed that students, teachers and administrative staff use the enabling strategy "development of problem solving skills". In addition, teachers also use "giving of information about recent political, social and scientific changes in the society". Teachers and administrative staff were also found to "give information only when absolutely necessary". The findings also showed that students and teachers and teachers and administrative staffs significantly differ in their perception of SLU as a health promoting school in terms of healthy school policy and physical environments. In terms of the indicators personal health skill, health services and social environment, students and administrative staffs significantly differ in their perception of SLU as health promoting school. As to the indicator community relations, no significant differences were found in the perceptions of students, teachers and administrative staff.